The NALP3/Cryopyrin-Inflammasome Complex is Expressed in LPS-Induced Ocular Inflammation - José F. González-Benítez; Marco A. Juárez-Verdayes; Sandra Rodríguez-Martínez; Mario E. Cancino-Diaz; Francisco García-Vázquez; Juan C. Cancino-Diaz (Hindawi Limited, 2008)
In the inflammosome complex, NALP3 or NALP1 binds to ASC and activates caspase-1 which induces IL-1β. In murine LPS-induced ocular inflammation, the production of IL-1β is increased. We suggest that NALP3- or NALP1-inflammasome complex can be participating in the LPS-induced ocular inflammation. In this work, eye, brain, testis, heart, spleen, and lung were obtained from C3H/HeN mice treated with LPS for 3 to 48 hours, and the expression of NALP1b, NALP3, ASC, caspase-1, IL-1β, and IL-18 was determined. Infiltrated leukocytes producing IL-1β in the anterior chamber were found at 12-hour posttreatment. A high upregulated expression of NALP3, ASC, caspase-1, IL-1β, and IL-18 was found at the same time when infiltrated leukocytes were observed. NALP1b was not detected in the eye of treated mice. NALP3 was also overexpressed in heart and lung. These results suggest that NALP3-, but not NALP1-inflammosome complex, is participating in the murine LPS-induced ocular inflammation.